2007
DOI: 10.1016/j.joca.2007.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of articular chondrocyte proliferation and anionic glycoconjugate synthesis by glucosamine (GlcN), N-acetyl GlcN (GlcNAc) GlcN sulfate salt (GlcN.S) and covalent glucosamine sulfates (GlcN-SO4)

Abstract: The free amino group of GlcN seems responsible for inhibition of chondrocyte proliferation and PG synthesis. These effects were greater under higher concentrations of GlcN in AD vs AI conditions. GlcN.HCl behaves similarly to GlcN.S, but differential effects with GlcN-X,Y,Z(SO(4))(n) isomers were observed. Acetylation or sulfation of the GlcN amino group reverses or partially reverses, respectively, anti-proliferative effects of GlcN. Sulfation of GlcN, at positions 3 and 6 results in complex effects on AC pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…However, the increase of the concentration to 10 m M AGA monomer showed a remarkable reduction ( P < 0.05). The results of MTT indicated that exposure to GlcN inhibited cells proliferation, which was consistent with those obtained by other research groups 17, 37. The inhibitory effect of the GlcN molecule was attributed to the unsubstituted amino group.…”
Section: Resultssupporting
confidence: 91%
“…However, the increase of the concentration to 10 m M AGA monomer showed a remarkable reduction ( P < 0.05). The results of MTT indicated that exposure to GlcN inhibited cells proliferation, which was consistent with those obtained by other research groups 17, 37. The inhibitory effect of the GlcN molecule was attributed to the unsubstituted amino group.…”
Section: Resultssupporting
confidence: 91%
“…Specifically, prolonged exposure of primary chondrocytes to optimal concentrations of GlcN increased matrix production with concomitant inhibition of chondrocyte proliferation [46]. The GlcN concentration significantly affected cell behavior and adding GlcN led to a concentration-dependent decrease in bovine articular cartilage proliferation in hydrogel [46,47]. …”
Section: Resultsmentioning
confidence: 99%
“…Increased aggrecan and procollagen α 1 (II) expression has been observed with 2 mM glucosamine compared with 0.7 µM, whereas 15 mM glucosamine is inhibitory (Varghese et al 2007). On the other hand, the inhibition of PG synthesis in the presence of glucosamine has been also reported (de Mattei et al 2002;Uitterlinden et al 2006;Terry et al 2007). Cell and explant cultures might thus behave differently.…”
Section: Discussionmentioning
confidence: 87%